How to avoid fracture of the locking screw in modular revision arthroplasty of the hip using the MRP Titan Revision System - Theresa Semmelmann; Alexander Schuh; Horst Rottmann; Reinhard Schröder; Christopher Fleischmann; Stefan Sesselmann (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2020)
The use of modular femoral stems in primary and revision arthroplasty of the hip has become popular within the last decade. On the other hand modularity creates new potential problems like fretting, crevice and galvanic corrosion, component loosening, dissociation and fracture of modular prostheses. Recently a problem of fracture of a locking screw in revision arthroplasty of the hip using the MRP Titan Stem (Peter Brehm GmbH, Weisendorf, Germany) appeared. The aim of this study is to evaluate the meaning of surface contamination in respect to fracture mechanism. To avoid fracture of the screw M6 of the MRP Titan System we recommend cleaning the inner thread of the morse taper junction with saline solution before junction is fixed with the screw and the torque wrench.
Keywords: 330; MRP Titan; Fracture; Hip; Modular Stem; Locking Screw